A felzárkózás eszközei az észak-alföldi határrégió kisvárosaiban - Horváth, Anna (Közép-Európai Közlemények, 2023)
In recent years, settlements that are able to be successful and competitive even in the changed economic conditions have appeared in an increasing number in backward regions. The starting points of this development can be the small towns of the Hungarian countryside, which are able to stand out from their environment in terms of institutions, infrastructure, and even culture, thereby creating micro-centers in their catchment area. In my thesis, I am looking for the answer to what role the small towns on the border areas of the Northern Great Plain, namely Fehérgyarmat, Kisvárda, Vásárosnamény and Záhony, play in the development of their catchment area. In order to explore this, I first analyze the current role of cities: what socio-economic characteristics can be observed, what kind of natural and built environment it has, and what cultural role each district center has. After that, I will analyze the situation of the cities from a tourism point of view, and finally I will examine the application activity more closely and draw conclusions about the tourism role of the cities.